2022
DOI: 10.1177/23259671221079338
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of MRI in Diagnosing Concomitant Meniscal Injuries With Pediatric and Adolescent Acute ACL Tears

Abstract: Background: Preoperative diagnosis of concomitant meniscal tears in pediatric and adolescent patients with acute anterior cruciate ligament (ACL) deficiency is challenging. Purpose: To investigate the diagnostic performance of magnetic resonance imaging (MRI) in detecting meniscal injuries for pediatric and adolescent patients with acute ACL tears. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: The authors retrospectively identified patients aged ≤18 years who underwent acute ACL recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(123 reference statements)
1
4
1
Order By: Relevance
“…Our results are in agreement with previous studies reporting poorer performance of MRI to predict meniscal injuries present at acute ACL reconstruction [4,24]. In our study, meniscal tears were more likely to be missed on MRI in ACL-deficient knees compared to ACL-intact knees (13 vs. 9, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with previous studies reporting poorer performance of MRI to predict meniscal injuries present at acute ACL reconstruction [4,24]. In our study, meniscal tears were more likely to be missed on MRI in ACL-deficient knees compared to ACL-intact knees (13 vs. 9, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…Kocher et al found MRI had a sensitivity of 71% in partial ACL ruptures in adolescents [ 51 ]. In a larger cohort study in 2022, Dawkins et al reported MRI scanning had moderate diagnostic ability to predict meniscal injuries with associated ACL ruptures in adolescents [ 52 ]. The performance was particularly poor with lateral meniscal tears (51% sensitivity).…”
Section: Discussionmentioning
confidence: 99%
“…It appears true that, when ACL or meniscal injuries are present in isolation, MRI is highly sensitive and specific, but the diagnostic accuracy declines in cases where concomitant injuries are present [ 53 ]. The sensitivity declines to around 50–75% [ 52 , 54 , 55 , 56 ]. This could have significant implications for management.…”
Section: Discussionmentioning
confidence: 99%
“…Bag of frozen corn might be substituted. Applying a little amount of oil to the area before applying the ice pack may help prevent it from adhering to the skin 15 Applying oil to an afflicted region that has recently been wounded or sutured is not a good idea. Instead, place a plastic bag over the area and cover it with the bag to avoid it becoming wet.…”
Section: Introductionmentioning
confidence: 99%